Critical temperature-sensitive salt synergistic ultra-high temperature oil well cement fluid loss agent and preparation method thereof

By using critical temperature-sensitive salt-efficient ultra-high temperature oil well cement loss-reducing agent, the problem of existing water loss-reducing agent failure under ultra-high temperature and ultra-high temperature conditions is solved, and effective water loss control of cement slurry and improvement of engineering performance is achieved.

CN119735739AActive Publication Date: 2025-04-01SICHUAN HONGSHENG PETROLEUM ENG TECH SERVICE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411904549.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing oil well cement water loss agent has problems such as high-temperature chain breakage, functional group degradation, high-temperature desorption, and high-temperature dehydration under ultra-high temperature, ultra-high temperature and alkaline conditions, and cannot fully meet the cementing engineering requirements of ultra-deep wells and ultra-deep wells.

Method used

The critical temperature-sensitive salt-efficient ultra-high temperature oil well cement water loss reduction agent is made of six raw material monomers: N,N-dimethacrylamide, vinylpyrrolidone, sodium p-acrylamide benzoate, acryloylmorphine, sodium methylallylsulfonate, and sodium 3-allyloxy-2-hydroxy-1-1 propanesulfonate. By improving the molecular structure design, the temperature and salt resistance are enhanced.

Benefits of technology

The water loss agent exhibits a good temperature-sensitive effect under ultra-high temperature conditions and has low water loss. It can effectively control the water loss of cement slurry, meet the needs of ultra-high temperature and ultra-high temperature cementing projects, and has good compatibility and engineering performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735739A_ABST
    Figure CN119735739A_ABST
Patent Text Reader

Abstract

The invention discloses a critical temperature-sensitive salt synergistic extra-high temperature oil well cement fluid loss agent and a preparation method of the critical temperature-sensitive salt synergistic extra-high temperature oil well cement fluid loss agent. The preparation method comprises the following steps: adding six raw material monomers including N, N-dimethylacrylamide, vinyl pyrrolidone, sodium p-acrylamido benzoate, acryloylmorphine, sodium methylallylsulfonate and 3-allyloxy-2-hydroxy-1-1 sodium propanesulfonate into water, and stirring for dissolving to obtain a reaction solution; s2, heating the reaction solution to 65 + / -2 DEG C, dropwise adding an initiator solution within 3-5 minutes, and then carrying out constant-temperature reaction at 80 + / -2 DEG C for 4 hours; s3, adding a terminator thiourea solution after the reaction time reaches 4 hours, and terminating the reaction; and starting circulating cooling water, and cooling to below 40 DEG C while stirring to obtain a solution, namely the fluid loss agent. The fluid loss agent disclosed by the invention has hydrophilic criticality, can form a temperature-sensitive synergistic effect at a high temperature and a salting-out synergistic effect at a high salt, and is particularly suitable for ultrahigh-temperature, ultrahigh-temperature and saturated salt water well cementation cement slurry systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil drilling, in particular to a critical temperature-sensitive salt-enhanced ultra-high temperature oil well cement fluid loss reducer and a preparation method thereof. Background Art

[0002] The process of injecting cement slurry into the annular space between the wellbore formed by drilling and the lowered casing, and solidifying the cement slurry to isolate the formation fluid is called cementing. Cementing provides the basic conditions for subsequent oil and gas well production increase, production layer transformation, well repair and other projects. It is a key link in the oil and gas well construction process and is related to the life of the oil and gas well, production and comprehensive economic benefits.

[0003] During the cementing process in oil fields, when cement slurry flows through permeable formations, its liquid phase percolates into the formation under the action of pressure difference. This phenomenon is called water loss of cement slurry. Excessive water loss of cement slurry not only pollutes the oil and gas layers, reduces the production of oil and gas wells, and affects the consistency between the performance of downhole cement slurry and the designed performance, but also may cause cementing accidents such as bridge plugging, air channeling, "flagpole insertion", and "sausage filling". Usually, oil well cement fluid loss reducer is added to the cementing cement slurry system to control water loss. Oil well cement fluid loss reducer is one of the three main admixtures that must be used in cementing cement slurry system.

[0004] With the reduction of shallow and medium-layer oil and gas resources, oil and gas exploration and development are developing towards deep oil reservoirs, ultra-deep oil reservoirs, complex formations, deep-sea oil reservoirs and other oil and gas reservoirs with harsh conditions. The harsh conditions faced in cementing, such as high temperature (120℃~150℃), ultra-high temperature (150℃~180℃), ultra-high temperature (180℃~260℃), saline layer, salt-gypsum layer, etc., are becoming more and more common. For example, the bottom static temperature of the oil layer in ultra-deep wells above 10,000 meters can reach 230℃~250℃, and the corresponding circulation temperature reaches 180℃~220℃; some areas with large geothermal gradients, such as Shengke 1 well in the eastern region, with a depth of 7026m and a bottom static temperature of 235℃, and Gulong 1 well in Daqing Oilfield, with a depth of 6300m and a maximum temperature of 232℃. Oil well cement fluid loss reducers have problems such as high temperature chain scission, functional group degradation, high temperature desorption, and high temperature dehydration under ultra-high temperature, ultra-high temperature and alkaline conditions, which makes oil well cement fluid loss reducers unable to fully meet the requirements of ultra-deep well and ultra-deep well cementing projects in terms of water loss control, temperature stability, and salt resistance. Based on the action mechanism, failure causes, and group chemical properties of fluid loss reducers, starting from molecular structure design, fundamentally solving its temperature and salt resistance problems is a feasible method for developing ultra-high temperature and salt resistant oil well cement fluid loss reducers. Summary of the invention

[0005] In view of the problems of high-temperature chain scission, functional group degradation, high-temperature desorption, high-temperature dehydration, etc. of current oil well cement fluid loss reducers under ultra-high temperature, extra-high temperature and alkaline conditions, the present invention provides a critical temperature-sensitive salt-enhanced ultra-high temperature oil well cement fluid loss reducer.

[0006] The critical temperature-sensitive salt-enhanced ultra-high temperature oil well cement fluid loss reducer provided by the present invention is prepared by copolymerizing six raw material monomers of N,N-dimethylacrylamide, vinyl pyrrolidone, sodium p-acrylamidobenzoate, acryloylmorphine, sodium methyl allyl sulfonate, and sodium 3-allyloxy-2-hydroxy-1-1 propane sulfonate in a mass ratio of (330-370): (40-60): (3-7): (35-45): (10-14): (25-35). The preparation method is as follows:

[0007] S1. Add six raw material monomers, namely, N,N-dimethylacrylamide, vinyl pyrrolidone, sodium p-acrylamidobenzoate, acryloylmorphine, sodium methyl allyl sulfonate, and sodium 3-allyloxy-2-hydroxy-1-1-propanesulfonate, into water, stir and dissolve to obtain a reaction solution;

[0008] S2. Raise the temperature of the reaction solution to 65°C ± 2°C, add the initiator solution dropwise within 3 to 5 minutes, and then react at a constant temperature of 80°C ± 2 for 4 hours;

[0009] S3. After the reaction time reaches 4 hours, add the terminator thiourea solution to terminate the reaction; and start the circulating cooling water, and cool down to below 40°C while stirring. The obtained solution is the fluid loss reducer.

[0010] Preferably, the initiator is sodium persulfate, and the amount of the initiator used is 1.5% of the total mass of the six monomers, and is added into water and dissolved to obtain an initiator solution with a mass percentage concentration of 25%.

[0011] Preferably, in step S2, the reaction temperature can be controlled not to exceed 82° C. by circulating cooling water during the reaction.

[0012] Preferably, the thiourea solution is an aqueous solution formed by dissolving thiourea in water with a mass percentage concentration of 8%, and the amount of thiourea used is 0.1% of the total mass of the six monomers.

[0013] Preferably, in the entire reaction system, the mass ratio of water to the total mass of the six monomers is 76:14. The water includes the total amount of water used in step S1 and the water in the initiator solution and the thiourea solution.

[0014] The preparation reaction principle formula of the fluid loss reducer is as follows:

[0015]

[0016] The main technical improvements of the fluid loss reducer of the present invention are as follows: (1) hydrophilic criticality, temperature-sensitive dehydration effect and salting-out effect are generated by the benzene ring, pyrrole ring and morphine ring structures in the fluid loss reducer molecules, so as to promote the adsorption of the fluid loss reducer molecules on the surface of cement particles, turn unfavorable factors into favorable factors, and improve the water loss control ability of the fluid loss reducer in the cement slurry system under ultra-high temperature and high salt conditions; (2) the high bond energy of the -CC-σ bond is utilized to solve the temperature stability of the main chain of the fluid loss reducer; (3) the two hydrogen atoms on the amidoamine are replaced by methyl groups with a power supply effect, and the power supply of the methyl groups is improved. The effect (weakening the tendency of the electron pair of the CN bond to lean toward the nitrogen atom) weakens the positive charge of the carbon atom, preventing the negatively charged hydroxyl group from attacking the positively charged carbon atom and causing hydrolysis, thus fundamentally solving the problem of the high-temperature degradation of the fluid loss reducer on the performance of the cement slurry; (4) The weakly polar bond is used to connect the temperature- and salt-resistant sulfonic acid group, thus avoiding the hydrolysis of the functional group in a high-temperature and high-alkaline environment, achieving the stability of the fluid loss reducer function and the engineering performance of the cement slurry system under ultra-high and extra-high temperature conditions, and solving the key technical problems of the consistency "thermal dilution", "bulging" and "stepping" during the thickening process of the cement slurry system.

[0017] Based on the above technical improvements, compared with the prior art, the fluid loss reducer of the present invention has the following beneficial effects:

[0018] (1) The fluid loss reducer prepared by the present invention has a critical hydrophilicity, and the critical hydrophilicity point for a weakly polar solvent (anhydrous ethanol) is 43.0%. It can form a temperature-sensitive synergistic effect at high temperature and a salting-out synergistic effect under high salt conditions, and is applicable to medium- and high-temperature cement slurry systems, as well as ultra-high temperature, extra-high temperature and saturated salt water cement slurry systems.

[0019] (2) The fluid loss additive prepared by the present invention has the ability to resist extremely high temperatures (250°C). 3 ) When the addition amount in the cement slurry system is 8.0%, the API water loss is 45.6mL (reaching the industry standard first-class product requirement: ≤50mL).

[0020] (3) The hydrophilicity of the fluid loss reducer prepared by the present invention is relatively weak. According to the principle of like dissolves like, the high-temperature dehydration effect makes the fluid loss reducer tend to be distributed on the surface of cement particles, which can effectively block the pores of the filter cake. Therefore, under the same dosage, the water loss increases only slightly with the increase of temperature. Considering that the higher the temperature, the more intense the thermal motion of water molecules (inherent characteristics) can cause a greater increase in water loss, the fluid loss reducer actually has a high-temperature synergistic effect (low water loss), especially at high temperature (above 150°C), ultra-high temperature (above 180°C), and ultra-high temperature (250°C), it shows a good temperature-sensitive effect.

[0021] (4) The fluid loss reducer prepared by the present invention has good compatibility with other commonly used cement additives and has no adverse effects on the rheology, stability, thickening time, strength and other properties required for cementing engineering of cement slurry; it can be used to prepare 250°C ultra-high temperature cement slurry system and high-density, low-density and other cement slurry systems.

[0022] (5) The synthesis method of the fluid loss reducer of the present invention is simple and easy to operate, and the raw materials are reasonably priced and easily available, which is convenient for industrial promotion.

[0023] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the infrared spectrum of the fluid loss additive prepared in Example 1.

[0025] Figure 2 This is the HNMR spectrum of the fluid loss additive prepared in Example 1.

[0026] Figure 3 This is the thermal analysis diagram of the fluid loss additive prepared in Example 1.

[0027] Figure 4 This is the water loss trend diagram of cement slurry system under different salt contents.

[0028] Figure 5 This is the thickening curve of 4-1# formulation (180°C).

[0029] Figure 6 This is the thickening curve of 4-1# formulation (200℃).

[0030] Figure 7 This is the thickening curve of 4-3# formulation (220℃).

[0031] Figure 8 This is the thickening curve of 4-4# formulation (250℃). DETAILED DESCRIPTION

[0032] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0033] Example 1

[0034] A method for preparing a fluid loss additive comprises the following steps:

[0035] (1) Weigh: 50.31 kg of N,N-dimethylacrylamide (DMAM); 7.19 kg of vinyl pyrrolidone (NVP); 0.72 kg of sodium p-acrylamidobenzoate (AMBA); 5.75 kg of acrylamide morphine (AMPL); 1.73 kg of sodium methyl allyl sulfonate (MAS); and 4.31 kg of sodium 3-allyloxy-2-hydroxy-1-1-propanesulfonate (AHPS).

[0036] (2) Weigh 1.05 kg of initiator sodium persulfate (Na2S2O8); dissolve it in 2.95 kg of water for later use;

[0037] (3) Weigh 0.080 kg of thiourea [(NH2)2S] as the terminator and dissolve it in 0.920 kg of water for later use;

[0038] (4) Add 430.0 kg of water to the reactor, add all six monomers to the reactor, and stir for 30 minutes to completely dissolve them; then heat the contents in the reactor to 65°C ± 2°C, and drop the initiator solution into the contents in the reactor within 3 to 5 minutes; after the addition of the initiator is completed, control the contents in the reactor to react at 80°C ± 2°C for 6 hours;

[0039] (5) After 6 hours of reaction, the terminator thiourea solution was added to the reactor material at one time to terminate the reaction; and the circulating cooling water was turned on and the temperature was lowered to below 40°C under stirring to obtain a fluid loss additive product, which was numbered BS100L-CT.

[0040] Example 2

[0041] A method for preparing a fluid loss additive comprises the following steps:

[0042] (1) Weigh: 1006.16 kg of N,N-dimethylacrylamide (DMAM); 143.74 kg of vinyl pyrrolidone (NVP); 14.37 kg of sodium p-acrylamidobenzoate (AMBA); 114.99 kg of acrylamide morphine (AMPL); 35.40 kg of sodium methyl allyl sulfonate (MAS); and 86.24 kg of sodium 3-allyloxy-2-hydroxy-1-propanesulfonate (AHPS).

[0043] (2) Weigh 2.10 kg of initiator sodium persulfate (Na2S2O8); dissolve it in 59.00 kg of water for later use;

[0044] (3) Weigh 1.60 kg of thiourea [(NH2)2S] as the terminator and dissolve it in 18.4 kg of water for later use;

[0045] (4) 8600.0 kg of water was added to the reactor, and all six monomers were added to the reactor, and stirred for 30 min to completely dissolve them; then the contents of the reactor were heated to 65°C ± 2°C, and the initiator solution was added dropwise to the contents of the reactor within 3 to 5 min; after the addition of the initiator was completed, the contents of the reactor were controlled to be kept at 80°C ± 2°C for 6 h;

[0046] (5) After the reaction has been going on for 6 hours, a terminator thiourea solution is added to the materials in the reactor at once to terminate the reaction; and circulating cooling water is turned on to cool the mixture to below 40° C. while stirring to obtain a fluid loss additive product.

[0047] The critical temperature-sensitive salt-enhanced ultra-high temperature oil well cement fluid loss reducer BS100L-CT prepared in Example 1 was repeatedly dissolved and purified by precipitation with acetone and water to remove unreacted monomers and by-products in the system; shredded, dried, and ground into powder; a certain amount of powder product was used to characterize the molecular structure by infrared spectroscopy and nuclear magnetic resonance hydrogen spectrum; the results are shown in Figure 1 , Figure 2 A certain amount of powder product was used to perform thermal scanning in the range of 25℃~650℃ to characterize its thermal stability. The results are shown in Figure 3 .

[0048] Figure 1 The infrared spectrum of -1 ~3600cm -1 It is the vibration peak of water molecules and alcohol hydroxyl groups adsorbed by the dehydration agent; 2933cm -1 The CH stretching vibration peaks of the main chain -CH3, -CH2-, -CH-; 2130cm -1 1630cm-1 is the peak of benzene ring double bond stretching vibration; -1 is the carbonyl C=O vibration peak; 1546cm -1 Compared with the C=O vibration peak in alkanone; 1457cm -1 -COO- stretching vibration peak; 1405cm -1 is the CN vibration peak of the amide group; 1365cm -1 C-OH stretching vibration peak; 1188cm -1 It is the CN stretching vibration peak in morphine; 1112cm -1 -O- stretching vibration peak; 1042cm -1 、622cm -1 It is the characteristic peak of sulfonic acid group; 569cm -1 The out-of-plane bending vibration peak of the CH of the benzene ring.

[0049] Figure 2The nuclear magnetic hydrogen spectrum was analyzed as follows: δ=7.9 is the amide -CO-NH- hydrogen peak in sodium acrylamidobenzoate; δ=7.8 is the hydrogen peak of the benzene ring; δ=4.7 is the solvent peak; 3.6 singlet is the hydrogen peak on the hydroxyl carbon; 2.7-3.1 quartet is the hydrogen peak of the carbon atom connected to the N atom in vinyl pyrrolidone and acryloylmorphine; 2.6 singlet hydroxyl hydrogen peak; 1.2~1.8 multiplets are the methylene (C-CH2-C) and methylene (C-CH-C) hydrogen atoms in the main chain and the alkyl hydrogen peaks in bis(methacrylamide) and sodium methyl allyl sulfonate.

[0050] Depend on Figure 3 Thermal analysis shows that: 8% weight loss at 25℃~320℃ is due to the loss of polymer adsorbed water and crystallized water; the starting decomposition temperature is 320℃, 320℃~330℃ is the thermal decomposition of amide groups, sulfonic acid groups and other groups on the fluid loss reducer polymer, 330℃~340℃ is the thermal decomposition of the fluid loss reducer polymer main chain; the thermal stability of the fluid loss reducer is 320℃.

[0051] Figure 1 and Figure 2 The infrared spectrum and nuclear magnetic hydrogen spectrum showed that the characteristic peaks of the functional groups of the fluid loss reducer appeared in both the infrared and nuclear magnetic spectra, indicating that all the selected monomers participated in the polymerization reaction and the synthesized fluid loss reducer was the expected target molecule. Figure 3 Thermal analysis shows that the fluid loss agent has excellent temperature resistance, and its thermal stability reaches 320°C. It will not thermally decompose under ultra-high temperature (200-250°C) conditions, which can effectively ensure the temperature resistance of the fluid loss agent.

[0052] The performance test of the fluid loss additive prepared in Example 1 is as follows:

[0053] The engineering performance of cement slurry was evaluated according to the industry standard SY / T5504.2-2013 "Evaluation Methods for Oil Well Cement Admixtures Part 2 Fluid Loss Reducers" and the national standard GB / T 19139-2015 "Test Methods for Oil Well Cement". The experiment involved retarder BS200R-G, expansion agent BS500, flow pattern regulator CT-18, and defoamer BP-1, all of which are oil well cement admixtures produced and widely used by Sichuan Hongsheng Petroleum Engineering Technology Service Co., Ltd.

[0054] (1) Hydrophilicity criticality test

[0055] According to the action principle of fluid loss reducer, the distribution of fluid loss reducer on the surface of cement particles is a key factor in controlling water loss. The hydrophilicity of the fluid loss reducer polymer is adjusted to make it tend to be dissolved in the critical state of water. Under high temperature and high salt conditions, it is promoted to distribute on the surface of cement particles, which can enhance its ability to control water loss. It is a simple, intuitive and feasible method to judge the hydrophilicity of the fluid loss reducer by observing its precipitation by forming different affinity solvents with water and relatively weak hydrophilic solvents (anhydrous ethanol). Take a certain amount of 5.0% water loss reducer aqueous solution, add a certain amount of anhydrous ethanol to it with a burette under stirring until it becomes turbid or precipitates, and examine its hydrophilicity and critical clear water point. In this experiment, three raw material monomers commonly used in the industry for preparing fluid loss reducers, acrylamide (AM), acrylic acid (AA), and 2-acrylamido-2-dimethylpropanesulfonate sodium (AMPS) were selected as raw material monomers to prepare terpolymers as comparative samples. According to the same preparation method as Example 1, the terpolymer finally prepared was named polymer A. Among them, the mass ratio of AM, AA, and AMPS is 3:1:5. The amount of initiator is 2.0% of the total mass of the three monomers. The amount of thiourea is 0.1% of the total mass of the three monomers. In the entire reaction system, the mass ratio of water to the total mass of the three monomers is 74:16. The experimental results are shown in Table 1.

[0056] Table 1. Experimental data table of hydrophilicity criticality evaluation of fluid loss reducer

[0057]

[0058] According to the experimental results in Table 1, combined with the analysis of the molecular structure characteristics of the fluid loss reducer, it can be seen that for the common fluid loss reducer copolymer A, although the main chain of the fluid loss reducer is non-hydrophilic, the common fluid loss reducer copolymer A contains a large number of strongly hydrophilic sulfonic acid groups and carboxyl groups, so it has almost no hydrophilic criticality in the weak polar ethanol solvent. For the fluid loss reducer BS100L-CT of the present invention, in addition to the main chain having non-hydrophilicity, a certain amount of lipophilic groups or weak hydrophilic groups such as benzene rings, pyrrole rings, and morphine rings are introduced. Therefore, it shows strong non-hydrophilicity in weak polar ethanol dissolution, and the weak polar ethanol solution shows a critical hydrophilic point of 43.0% in volume ratio. This proves that the synthesized fluid loss reducer of the present invention has a certain hydrophilic criticality.

[0059] (2) Temperature sensitivity test evaluation

[0060] According to the working principle of fluid loss reducers, the distribution of fluid loss reducers on the surface of cement particles is a key factor in controlling water loss. By adjusting the hydrophilicity of the fluid loss reducer polymer so that it tends to a certain critical state of dissolution in water, and promoting its distribution on the surface of cement particles under high temperature and high salt conditions, its ability to control water loss can be enhanced. The hydrophilicity of fluid loss reducers is relatively weak, and on the one hand, the high-temperature dehydration effect is more obvious; on the other hand, due to the weak hydrophilicity of fluid loss reducers, according to the principle of like dissolves like, fluid loss reducers tend to be distributed on the fluid loss reducer adsorption layer with the same affinity and adsorbed on the surface of cement particles, and its water loss control ability is enhanced. The same amount of fluid loss reducer is added to the conventional density cement slurry system, and the change of water loss of the cement slurry system with temperature is examined, and different types of fluid loss reducers are compared and examined to see whether they have temperature-sensitive effects. 60℃~105℃ conventional density cement slurry formula: G-grade high sulfur resistance oil well cement 800.0g + 5.0% fluid loss agent + 1.0% retarder BS200R-G + 2.0% expansion agent BS500 + 1.5% flow pattern regulator TC-18 + 0.5% defoamer BP-1 + water; 120℃~220℃ conventional density cement slurry formula: G-grade high sulfur resistance oil well cement 500.0g + high temperature stabilizer (quartz sand) 250.0g + fluid loss agent + 5.0%~7.0% retarder BS200R-G + 2.0% expansion agent + 1.5% flow pattern regulator TC-18 + 0.5% defoamer BP-1 + water. The experimental results are shown in Table 2.

[0061] Table 2. Experimental data table of temperature sensitivity evaluation of fluid loss reducer

[0062]

[0063] According to the experimental results in Table 2, combined with the molecular structure characteristics of the fluid loss agent and the analysis of the action principle of the fluid loss agent, it can be seen that for the common high-temperature resistant fluid loss agent copolymer A, on the one hand, due to its strong hydrophilicity, the fluid loss agent produced by thermal desorption and dehydration is distributed in the water phase, and the viscosity of the water phase containing the fluid loss agent decreases sharply with the increase of temperature; on the other hand, the higher the temperature, the more violent the thermal motion of water molecules; therefore, at the same dosage, the water loss increases with the increase of temperature, especially at high temperature (above 150°C) and ultra-high temperature (above 180°C), the water loss increases significantly, and to better control the water loss, it is necessary to increase the amount of the fluid loss agent. For the critical temperature-sensitive high-temperature resistant fluid loss reducer BS100L-CT, due to its weak hydrophilicity, according to the principle of similar compatibility, the high-temperature dehydration effect makes the fluid loss reducer tend to be distributed on the surface of cement particles, which can effectively block the pores of the filter cake. Therefore, at the same dosage, the water loss increases only slightly with the increase of temperature. Considering that high temperature makes the thermal motion of water molecules more intense (inherent characteristics), which can cause a greater increase in water loss, the fluid loss reducer actually has a high-temperature synergistic effect; especially at high temperature (above 150°C) and ultra-high temperature (above 180°C), it shows a good temperature-sensitive effect (low water loss).

[0064] (3) Salt enhancement test evaluation

[0065] In general, the water loss in the cement slurry system to which a conventional fluid loss reducer is added will increase significantly with the increase in salt content. Salt enhancement means that the ability of the fluid loss reducer to control water loss will not weaken or further enhance with the increase in salt content. The currently commonly used high-temperature fluid loss reducer copolymer A was used in an experimental comparison with the fluid loss reducer BS100L-CT of the present invention. When the water loss increase does not exceed 10mL or further decreases under the same conditions, it is judged to be salt enhanced. Cement slurry system formula: 500.0g of G-grade high-sulfur resistant oil well cement + 250.0g of high-temperature stabilizer (quartz sand) + 8.0% fluid loss reducer + 7.0% retarder BS200R-G + 2.0% expansion agent BS500 + 1.5% flow pattern regulator TC-18 + 0.5% defoaming agent BP-1 + water; the experimental temperature is 200°C. The experimental results are shown in Tables 3 and Figure 4 shown.

[0066] Table 3. Formula of conventional density brine cement slurry system

[0067]

[0068] According to Table 3 and Figure 4The experimental results, combined with the molecular structure characteristics of the fluid loss agent and the analysis of the action principle of the fluid loss agent, show that for the conventional structure fluid loss agent copolymer A, as the salt (NaCl) concentration increases, the water loss increases sharply; the first stage of the sharp increase in water loss is when the salt concentration is below 7.5%. This stage is mainly caused by the curling of the fluid loss agent caused by the ionic atmosphere of the salt cations shielding the anions of the fluid loss agent; the second stage of the sharp increase in water loss is when the salt concentration reaches about 10.0% to 15.0%. At this stage, the water loss of the cement slurry system is mainly caused by the salting-out effect that causes the fluid loss agent molecules to separate and precipitate from the water phase; the third stage of the increase in water loss is when the salt concentration is 15.0% to 26.5% (saturated brine). At this stage, the increase in water loss is mainly caused by the salting-out effect that makes the fluid loss agent curl more tightly and precipitate more completely, but this effect is much smaller than that from the dissolved state to the precipitated state, so the effect on water loss is small at low concentrations, and the increase in water loss is slightly slower than the first two stages. For the fluid loss reducer BS100L-CT of the present invention, the first stage of water loss increase is when the salt concentration is 0-7.5%, which is mainly due to the ion atmosphere effect generated after the salt is ionized in water, which causes the fluid loss reducer molecules in the water phase to curl and the viscosity of the water phase to decrease; the water loss of the cement slurry system is slightly reduced in the salt concentration stage of 7.5-26.5% (saturated brine), mainly because its structure has benzene rings, pyrrole rings, and morphine ring groups with weak hydrophilicity and obvious salting-out effect. The curled fluid loss reducer polymer and precipitated fluid loss reducer polymer produced by the salting-out effect are more distributed on the surface of cement particles according to the principle of like dissolves like, and can effectively block the pores of the filter cake, thereby reducing water loss. However, since most of the fluid loss reducer has been precipitated at a certain initial salting-out precipitation concentration (about 7.5%), further increasing the salt concentration can only cause a small amount of polymer to further precipitate and the polymer to curl and precipitate more tightly, but this effect is much smaller than that from the dissolved state to the precipitated state, and has little effect on the water loss control ability, so the water loss is slowly reduced. The experimental results show that the synthesized fluid loss agent of the present invention has a salt enhancement effect, and the critical concentration of salt enhancement is about 7.5%.

[0069] (4) Comprehensive performance evaluation of fluid loss additives

[0070] In actual cementing projects, each well faces different engineering conditions and requirements, requiring cement slurry systems with different properties, such as different densities, different temperatures, etc. Different cement slurry systems were prepared with the synthetic fluid loss agent BS100L-CT, and the comprehensive engineering performance of the fluid loss agent at conventional density was investigated in the range of 180℃~250℃. The experimental formula is shown in Table 4, and the types of various raw materials are the same as above; the experimental results are shown in Tables 5 and Figure 5-8 .

[0071] Table 4. Formulas of ultra-high temperature, extra-high temperature and conventional density cement slurry systems

[0072]

[0073] Note: The expansion agent in Table 4 is expansion agent BS500. The types of other additives are the same as those used in the previous experiments.

[0074] Table 5. Experimental data of comprehensive engineering performance of ultra-high temperature, extra-high temperature and conventional density cement slurry systems

[0075]

[0076] Table 5 and Figure 5-8 The experimental results show that the synthesized fluid loss reducer BS100L-CT of the present invention can be used to prepare a conventional density ultra-high temperature and extra-high temperature cementing cement slurry system by properly adjusting the amount of fluid loss reducer and retarder and adding an expander, a flow pattern regulator and a defoamer. The engineering performance indicators of the cement slurry system such as water loss, rheology, free liquid, thickening time, compressive strength, and gravity stability meet the requirements of industry standards.

[0077] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A critical temperature-sensitive salt-enhanced ultra-high temperature oil well cement fluid loss reducer, characterized in that: It is prepared by copolymerizing six raw material monomers of N,N-dimethylacrylamide, vinyl pyrrolidone, sodium p-acrylamidobenzoate, acryloylmorphine, sodium methyl allyl sulfonate and sodium 3-allyloxy-2-hydroxy-1-1 propane sulfonate in a mass ratio of (330-370): (40-60): (3-7): (35-45): (10-14): (25-35); the molecular structure of the fluid loss reducer is as follows:

2. A method for preparing the critical temperature-sensitive salt-enhanced ultra-high temperature oil well cement fluid loss reducer as claimed in claim 1, characterized in that: The following steps are involved: S1. Add six raw material monomers, namely, N,N-dimethylacrylamide, vinyl pyrrolidone, sodium p-acrylamidobenzoate, acryloylmorphine, sodium methyl allyl sulfonate, and sodium 3-allyloxy-2-hydroxy-1-1-propanesulfonate, into water, stir and dissolve to obtain a reaction solution; S2. Raise the temperature of the reaction solution to 65°C ± 2°C, add the initiator solution dropwise within 3 to 5 minutes, and then react at a constant temperature of 80°C ± 2 for 4 hours; S3. After the reaction time reaches 4 hours, add the terminator thiourea solution to terminate the reaction; and start the circulating cooling water, and cool down to below 40°C while stirring. The obtained solution is the fluid loss reducer.

3. The method for preparing the critical temperature sensitive salt enhanced ultra-high temperature oil well cement fluid loss reducer according to claim 2, characterized in that: The initiator is sodium persulfate, and the amount of the initiator used is 1.5% of the total mass of the six monomers, and is dissolved in water to form an initiator solution.

4. The method for preparing the critical temperature sensitive salt enhanced ultra-high temperature oil well cement fluid loss reducer according to claim 2, characterized in that: In step S2, during the reaction process, the reaction temperature is controlled not to exceed 82° C. by circulating cooling water.

5. The method for preparing the critical temperature sensitive salt enhanced ultra-high temperature oil well cement fluid loss reducer according to claim 2, characterized in that: The thiourea solution is a solution formed by dissolving thiourea in water, and the amount of thiourea used is 0.1% of the total mass of the six monomers.

6. The method for preparing the critical temperature sensitive salt enhanced ultra-high temperature oil well cement fluid loss reducer according to claim 2, characterized in that: In the entire reaction system, the mass ratio of water to the total mass of six monomers is 76:14.

Citation Information

Patent Citations

  • Water-loss control agent for oil-well cement and preparation method thereof

    CN104531112A

  • High-temperature-resistant salt-resistant water loss reducer and preparation method and application thereof

    CN108929405A

  • Ultrahigh-temperature well cementation cement slurry fluid loss agent as well as preparation method and application thereof

    CN115725030A

  • Method for producing a polymeric conversion product

    US20030018137A1